Feasibility of high-throughput drug sensitivity screening (HDS)-guided treatment for children with refractory or relapsed acute myeloid leukemia - Lv, Wenxiu; Chen, Tianping; Wang, Shen; Li, Chun; Zhang, Bo; Wang, Liang; Xv, Fang; Cao, Fang; Wang, Jing; Chen, Li; Liao, Chenglin; Li, Na; et al. (Frontiers in Pediatrics, 2023)
Relapsed/refractory (rel/ref) acute myeloid leukemia (AML) has a very high mortality rate. At present, hematopoietic stem cell transplantation (HSCT) is the most effective treatment for rel/ref AML. The remission of the primary disease before HSCT is crucial to the effect of transplantation. Therefore, it is critical to choose suitable chemotherapy before HSCT. We recorded the outcomes of high-throughput drug sensitivity screening (HDS) in children with rel/ref AML. Thirty-seven paediatric rel/ref AML patients who received HDS from September 2017 until July 2021 were analyzed retrospectively. Most of the patients (24 patients, 64.9%) had adverse cytogenetics. Two patients had rel/ref AML with central nervous system leukemia. The complete remission (CR) rate was 67.6%. Eight patients developed Ⅳ grade bone marrow suppression. Twenty-three patients (62.2%) had undergone HSCT. The 3-year overall survival (OS) and EFS rate were 45.9% and 43.2%, respectively. Infection in myelosuppression stage was the main cause of death. The outcome of HDS was superior to the commonly reported rates. These results suggest that HDS may be a novel treatment option in paediatric patients with rel/ref AML, and it is a promising transitional regimen prior to HSCT.